On‐Chip Metamaterial‐Enhanced Mid‐Infrared Photodetectors with Built‐In Encryption Features - Shicong Hou; Li Han; Shi Zhang; Libo Zhang; Kaixuan Zhang; Kening Xiao; Yao Yang; Yunduo Zhang; Yuanfeng Wen; Wenqi Mo; Yiran Tan; Yifan Yao; et al. (Advanced Science)
Abstract The integration of mid‐infrared (MIR) photodetectors with built‐in encryption capabilities holds immense promise for advancing secure communications in decentralized networks and compact sensing systems. However, achieving high sensitivity, self‐powered operation, and reliable performance at room temperature within a miniaturized form factor remains a formidable challenge, largely due to constraints in MIR light absorption and the intricacies of embedding encryption at the device level. Here, a novel on‐chip metamaterial‐enhanced, 2D tantalum nickel selenide (Ta₂NiSe₅)‐based photodetector, meticulously designed with a custom‐engineered plasmonic resonance microstructure to achieve self‐powered photodetection in the nanoampere range is unveiled. Gold cross‐shaped resonators are demonstrated that generate plasmon‐induced ultrahot electrons, significantly enhancing the absorption of MIR photons with energies far below the bandgap and boosting electron thermalization in Ta₂NiSe₅, yielding a 0.1 V bias responsivity of 47 mA/W—an order of magnitude higher than previously reported values. Furthermore, the implementation of six reconfigurable optoelectronic logic computing (“AND”, “OR”, “NAND”, “NOR”, “XOR”, and “XNOR”) are illustrated via tailored optical and electrical input‐output configurations, thereby establishing a platform for real‐time infrared‐encrypted communication. This work pioneers a new direction in secure MIR communications, advancing the development of high‐performance, encryption‐capable photonic systems.